Integrating Vocationalogy-Based Web Media with Blended Learning for Enhancing Practical Competence in Vocational Education - Andayani, Endah; Rulita Nurfaizana, Della; Agustina, Rini; Dameaty Hutagalung, Fonny (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: Vocational education requires learning media that not only support the delivery of conceptual knowledge but also facilitate hands-on practice relevant to workplace demands. Method : This study aims to develop and evaluate a blended learning web-based media called Vocationalogy, designed to support project-based learning in Creative Products and Entrepreneurship (PKK) at vocational high schools. Quantitative data were collected through surveys involving 94 students who used the platform during blended learning activities. Novelty: The study adopted the waterfall model as the framework for the development of the Vocationalogy platform, encompassing stages of analysis, design, development, implementation, and evaluation. The evaluation focused on four main aspects: usability, content quality, interactivity, and user satisfaction. Descriptive statistical analysis was used to assess the platform's effectiveness, and results were further validated through literature comparison and theory-driven interpretation. Result: The results indicated that Vocationalogy effectively enhanced students' access to practical materials, facilitated self-directed learning, and increased engagement through multimedia-based content and asynchronous discussion forums. Students reported high levels of satisfaction, particularly regarding the clarity of content and ease of use. The integration of features such as digital portfolios and self-assessment tools also supported reflective learning and competency tracking. In conclusion, the Vocationalogy platform demonstrates strong potential as an adaptive and pedagogically sound learning management system (LMS) for vocational education. Future development should focus on strengthening collaborative features and integrating learning analytics to enhance personalization and feedback mechanisms.